ANALISIS TEKNIKAL BITCOIN DENGAN METODE EXPONENTIAL MOVING AVERAGE, STOCHASTIC OSCILLATOR, DAN MACD - Yuangga, Aries
Bitcoin is a digital currency created in 2009 by Satoshi Nakamoto. Bitcoin is an attractive investment asset because it has fluctuating price movements with high volatility. The fundamental bitcoin is often regarded as digital gold. Bitcoin has a huge growth space compared to gold. On June 18th, 2020 total bitcoin market capitalization was valued at $ 173 million, while gold was valued at $ 9 trillion. In this Final Project, methods will be made to maximize investment in bitcoin trading using technical analysis methods. Technical analysis is an analytical technique known in the financial world that is used to predict market trends by means of historical market data, mainly of price and volume developments. Technical analysis can use various technical indicators. The indicators used in this study are Exponential Moving Average (EMA), Stochastic Oscillator, and Moving Average Convergence Divergence (MACD). Of the three technical indicators, three methods will be made to determine the buying and selling decision of bitcoin. Of the three methods that have been made, trading simulations will be carried out for a period of time from the beginning of 2017 to the end of 2019. Furthermore, the returns, profitable percentage, and frequency trading derived from each method will be compared. The higher the yield and percentage of profits obtained with the lower risk and lower number of trades made, the better the method. In this final project, the EMA method with a long & short strategy gives the best results with a net profit of 7727.45%, a maximum drawdown of 24.74%, a sharpe ratio of 0.541, a 41.67% profitable percentage, and 60 number of trades.